2021
DOI: 10.3390/antiox10040510
|View full text |Cite
|
Sign up to set email alerts
|

Control of Oxidative Stress in Cancer Chemoresistance: Spotlight on Nrf2 Role

Abstract: Chemoresistance represents the main obstacle to cancer treatment with both conventional and targeted therapy. Beyond specific molecular alterations, which can lead to targeted therapy, metabolic remodeling, including the control of redox status, plays an important role in cancer cell survival following therapy. Although cancer cells generally have a high basal reactive oxygen species (ROS) level, which makes them more susceptible than normal cells to a further increase of ROS, chemoresistant cancer cells becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 179 publications
1
45
0
Order By: Relevance
“…Mutations can also occur in the principal Nrf2 repressor, Keap1 or component of the E3 ubiquitin-ligase complex Cullin 3 (CUL3), with loss of function that renders these factors unable to bind Nrf2 and thus result in persistent Nrf2 activation [ 68 ].…”
Section: The Dual Role Of Nrf2 In Cancermentioning
confidence: 99%
“…Mutations can also occur in the principal Nrf2 repressor, Keap1 or component of the E3 ubiquitin-ligase complex Cullin 3 (CUL3), with loss of function that renders these factors unable to bind Nrf2 and thus result in persistent Nrf2 activation [ 68 ].…”
Section: The Dual Role Of Nrf2 In Cancermentioning
confidence: 99%
“…A mountain of evidence has suggested that redox imbalance and resulting lipid peroxidation products play an important role in cancer development, progression, metastasis, and chemoresistance. These findings, excellently presented in several reviews [ 56 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ], are far from being unique. For instance, scientists have highlighted some paradoxes relating to the two faces of ROS, which are able to both promote and suppress cancer [ 74 ].…”
Section: Oxidative Stress In Physiopathology and In Cancermentioning
confidence: 75%
“…Recently, in a large cohort of melanoma tumor samples with different degrees of malignancy, it was demonstrated that there was no correlation between immunostaining of the Nrf2 protein and mRNA expression levels [ 147 ]. Thus, very likely, post-translational mechanisms can account for the Nrf2 activation in melanoma [ 73 ]. Among these mechanisms, short noncoding RNAs, in particular microRNAs (miRNAs), are gaining attention for their ability to control gene expression.…”
Section: Oxidative Stress In Melanomamentioning
confidence: 99%
“…However, treatment with NRF2 activators may inactivate drug-induced oxidative stress that normally would result in cell death. Therefore, it is necessary to monitor their clinical efficacy, given that the activation of NRF2 may contribute to the development of chemoresistance [ 138 , 139 ]. Taken together, NRF2 activators have shown potential for cancer therapy, but further investigations are also needed to demonstrate their clinical efficacy, especially in combination with chemotherapeutic drugs.…”
Section: Antioxidant Therapeutic Strategies In Cancermentioning
confidence: 99%